Community-Based Training for Drug and Premarital Sex Awareness Among Teenagers in Sukabumi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Indonesia faces pressing social challenges related to drug abuse and premarital sex among teenagers. This community-based project aimed to provide essential knowledge and foster a comprehensive understanding of these dangers through interactive seminars, engaging questions, and educational games. The activity was conducted at Mts Tarbiyatul Falah, Tenjolaya Village, Cicurug, Sukabumi, West Java, on July 17–19. Sukabumi was specifically chosen as the project location due to its identification by BNN data as an area with high potential for drug trafficking and use. Furthermore, Mts Tarbiyatul Falah's 7th-grade students were identified as a crucial and receptive age group to be educated on the meanings and implications of free sex and drug abuse. This initiative was undertaken in close collaboration with the National Narcotics Agency (BNN), the Village Head, and the Principal of Mts Tarbiyatul Falah. During the seminars, materials on drug topic were delivered by the BNN Team, complemented by interactive games designed to reinforce comprehension. The seminar successfully engaged 130 participants, comprising 100 7th-grade students and 30 teachers. To making an impact based on evaluation results were highly encouraging: 86.67% of participants answered direct questions correctly, and the success rate, based on a comprehensive questionnaire, reached 75.45%. These outcomes collectively indicate a significant improvement in participants' understanding of the material presented.